Bank-Specific Factors Influencing Profitability of Islamic Banks in Bangladesh - Rahaman, Md Mustafizur; Akhter, Sharmin (Journal of Business and Technology (Dhaka), 2016)
This paper aims at empirically studying the impact of some selected bankspecific factors on Islamic banks profitability. The data for this study covering a period 2009-2013 is obtained from the annual reports of respective Islamic banks. The statistical tool employed is the technique of linear multiple regression analysis. The data-set used in this study involves eight Islamic banks operating in Bangladesh. Empirical results show that bank-size and deposit have significant negative impact on the return on assets (ROA) which is the proxy for Islamic banks profitability, while equity is found to have positive significant impact. However, loan and expense management are found to be insignificant in affecting the profitability of the banks. Journal of Business and Technology (Dhaka) Vol.10(1) 2015; 21-36